Assessment of the Level of Practical and Theoretical Knowledge as a Starting Point for the Implementation of Lean Hospital Concept - Anna Chmielarz; Beata Wieczorek-Wojcik; Agnieszka Zdęba-Mozoła; Remigiusz Kozłowski; Dorota Kilańska; Jan Krzysztof Solarz; Tomasz Czapla; Michał Marczak (Systems, 2023)
Background: The implementation of the Lean Hospitals concept can contribute to the improvement of internal processes in healthcare organizations. The level of a management team’s knowledge is an important part of effective implementation of Lean Hospital elements in hospitals. The purpose of this article is to determine the degree of theoretical and practical knowledge of Lean Hospitals (defined for the purposes of the study as a set of lean tools) among the management teams of Polish hospitals. The authors focused on examining the discrepancy between practical and theoretical knowledge to determine which of them is less prevalent in hospitals in order to correctly establish elements of the implementation procedures, which must be improved and perfected to more effectively implement the lean concept in healthcare. Methods: The research methods used to achieve the study objectives included, respectively, an analysis of the literature on the subject and gathering of data using the Qualtrics Platform with a CAWI survey. Respondents rated their level of knowledge regarding Lean Hospital tools on a Likert scale. Basic descriptive statistics and radar diagrams were used to analyze and present the data. Statistical analysis was performed using Excel spreadsheets. Results: It was established that the vast majority of management teams in the studied hospitals had limited basic knowledge about Lean Hospitals, if any. The greatest lack of knowledge was found in the field of practical (implementation) knowledge of Lean Hospital tools. The research found no significant discrepancy between the level of theoretical and practical knowledge at the level of general knowledge and detailed knowledge relating to the knowledge of individual lean tools. The standardized work tool was rated best in terms of self-assessing practical knowledge. The worst rated tools in terms of both theoretical and practical knowledge self-assessment were Kaizen, Kanban and TPM. Conclusions: The results of the conducted studies indicate a low level of knowledge and advancement in the implementation of the Lean Hospitals concept in selected Polish hospitals. Limited knowledge of the Lean Hospital concept was established for entire management teams. A low level of knowledge was noted in both theoretical and practical knowledge. Supplementing knowledge only at the theoretical level without taking care of the practical knowledge aspect may prolong the implementation procedure or stop it completely. Therefore, based on the result of the research, it can be concluded that the first stage of lean implementation in hospitals should focus on supplementing the knowledge and preparing the employees for work in a lean culture, diverting particular attention to the practical part of the training.